2020
DOI: 10.1111/petr.13909
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ selected peripheral blood Stem Cell Boost (SCB) for Poor Graft Function (PGF) or mixed chimerism in pediatric patients, after hematopoietic stem cell transplantation: Results of a retrospective multicenter study

Abstract: Background: PGF is historically associated with high morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT).Methods: In this study, we report our multicenter experience on stem cell boost (SCB) for PGF, or incomplete donor engraftment, in 16 pediatric patients. Donors were HLAmatched siblings (n = 4), unrelated donors (n = 11), or haploidentical family members (n = 1). Ten patients had two-lineage cytopenia, 5 had one-lineage cytopenia, and 1 had poor immunological reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…Therefore, these factors likely contributed to their favorable OS at last follow-up. Berger et al found that the majority of deaths occurred within the first 6 months of a SCB [2], consistent with our observation wherein six of the eight deaths occurred within the same timeframe.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, these factors likely contributed to their favorable OS at last follow-up. Berger et al found that the majority of deaths occurred within the first 6 months of a SCB [2], consistent with our observation wherein six of the eight deaths occurred within the same timeframe.…”
Section: Discussionsupporting
confidence: 92%
“…[7,23] In a recent large metanalysis of 209 adults who received a SCB for PGF, the overall pooled ORR, CR and PR were 80%, 72%, and 13%, respectively, but that study did not delineate the type of cytopenia pre-SCB. [6] While the CR rate in our study (29%) is lower than that and those from a few pediatric studies (50-79%) [2,10,12], it is similar to that reported by Mianaridi (36%) [11] and Chandra (25%) [3] (Table 3). Per the latter's report, only 1/3 of patients with MC respond to a SCB.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The disappointing clinical outcomes, with long-term survival rates of not much more than 20% [7], have largely curbed the enthusiasm for allogeneic "naked haplo" transplantation without immediate or delayed co-transplantation of an alloreactivity-attenuated T-cell product [7]. The use of CD34+ selected products is limited to correction of poor graft function following allogeneic hematopoietic stem cell transplantation [13][14][15][16]. In the autologous setting, CD34 selected transplants retain some relevance for tumor cell purging, such as in neuroblastoma [17,18].…”
Section: Introductionmentioning
confidence: 99%